PERENCANAAN SISTEM PENYALURAN DRAINASE DI KECAMATAN HAMPARAN RAWANG, KOTA SUNGAI PENUH - Rafianda Adela Putra; Eka Wardhani; Nico Halomoan (ENVIROSAN : Jurnal Teknik Lingkungan, 2019)
Hamparan Rawang District is one of the Districts in Sungai Penuh City that has floods. This indicates that the available drainage channels have not been able to cope with excess water due to flooding/inundation still occurring. Therefore it needs to be related to the causes of flooding in the Hamparan Rawang District. As a method used to use fact analysis and the relationships that occur in the field related to factors that cause floods. Based on the results of the causes of flooding in the Hamparan District, heavy and continuous rainfall, inadequate drainage system capacity and drainage channels are clogged with garbage. Keyword: flood, Drainage canal, Hamparan Rawang District